On the complexity of the ideal of absolute null sets - Zakrzewski, P. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
Answering a question of Banakh and Lyaskovska, we prove that for an arbitrary countable infinite amenable group $G$ the ideal of sets having $μ$-measure zero for every Banach measure $μ$ on $G$ is an $F_{σ δ}$ subset of $\{0,1\}^G$.